Cardiac Tamponade in a Hypothyroid Patient - Ditsataporncharoen, Pichai (Journal of Health Science of Thailand, 1995)
A Thai female patient was found having a sign and symptom of cardiac tamponade. She was treated by aspirating the fluid from pericardium (pericardiocentesis). It was a 550 cc. straw color fluid. Laboratory investigation of fluid and blood analysis led to the diagnosis of tuberculous pericarditis and hypothyroidism. The patient was treated with Anti-TB and Hypothyroid drugs until she improved and was discharged thereafter.